The coordinated action of glucuronoyl esterase and α‐glucuronidase promotes the disassembly of lignin–carbohydrate complexes. Issue 3 (10th January 2021) - Raji, Olanrewaju; Arnling Bååth, Jenny; Vuong, Thu V.; Larsbrink, Johan; Olsson, Lisbeth; Master, Emma R.
Abstract : Glucuronoxylans represent a significant fraction of woody biomass, and its decomposition is complicated by the presence of lignin–carbohydrate complexes (LCCs). Herein, LCCs from birchwood were used to investigate the potential coordinated action of a glucuronoyl esterase ( Tt CE15A) and two α‐glucuronidases ( Sde Agu115A and Axy Agu115A). When supplementing α‐glucuronidase with equimolar quantities of Tt CE15A, total MeGlc p A released after 72 h by Sde Agu115A and Axy Agu115A increased from 52% to 67%, and 61% to 95%, respectively. Based on the combined Tt CE15A and Axy Agu115A activities, 34% of MeGlc p A in the extracted birchwood glucuronoxylan was occupied as LCCs. Notably, insoluble LCC fractions reduced soluble α‐glucuronidase concentrations by up to 70%, whereas reduction in soluble Tt CE15A was less than 30%, indicating different tendencies to adsorb onto the LCC substrate. Abstract :